2011
DOI: 10.1016/j.ijgo.2011.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and neonatal survival and mortality in the Upper West Region of Ghana

Abstract: Maternal death notifications and audits are useful tools for improving quality of care and outcomes. With almost half of maternal deaths occurring within 24 hours of admission, emergency care in the Upper West Region of Ghana must be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 3 publications
2
32
0
1
Order By: Relevance
“…Of note, the four datasets from India were obtained from the same investigation [24]. The oldest dataset was from 1967 [24] and the most recent datasets were from 2009 [47, 62]. Thirty-one of the 44 datasets (70.5%) examined maternal deaths while the other 13 datasets (29.5%) examined perinatal deaths.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, the four datasets from India were obtained from the same investigation [24]. The oldest dataset was from 1967 [24] and the most recent datasets were from 2009 [47, 62]. Thirty-one of the 44 datasets (70.5%) examined maternal deaths while the other 13 datasets (29.5%) examined perinatal deaths.…”
Section: Resultsmentioning
confidence: 99%
“…A terceira demora é a que ocorre relacionada à qualidade da atenção na unidade de saúde em que medidas específicas, se não tomadas em momento oportuno, também podem ser a causa de desfechos não satisfatórios 14 . Embora o presente estudo não tenha especificamente investigado demoras, os achados potencialmente relacionados às demoras são similares a outros que abordam o mesmo tema 15,16 . Nesta série de casos predominaram causas obstétricas de óbito materno, o que geralmente ocorre na análise de dados de populações de países em desenvolvimento 17 e que se associa a deficiências na condução de casos, com possibilidade de reversão se atendidos de forma correta no momento ideal.…”
Section: Discussionunclassified
“…However, a combination of these factors is required for women to have a final say about issues pertaining to their healthcare utilisation [13, 14]. At the same time, it has been noted that low empowerment status curtails women's ability to access healthcare; for instance, an assessment of participation in Community-based Health Planning and Services (CHPS) in Ghana indicated that male dominance and limited women's access to services are rendered by the CHPS compounds [15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported inconsistent effects of women's decision-making autonomy on the use of health services [11, 1315]. This may be due to the fact that virtually all the existing studies aggregate three autonomy variables—control over finance, decision-making power, and extent of freedom of movement.…”
Section: Introductionmentioning
confidence: 99%